Isolasi dan Seleksi Cendawan Rhizosfer dan Endofit asal Tanaman Kelor sebagai Agens Penginduksi Perkecambahan pada Benih Padi: Isolasi dan Seleksi Cendawan Rhizosfer dan Endofit asal Tanaman Kelor sebagai Agens Penginduksi Perkecambahan pada Benih Padi - Hishar Mirsam; Masluki Masluki; Mutmainnah Mutmainnah (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Rhizosphere and endophytic fungi are functional types of microbes capable of producing secondary metabolites that can affect plant growth directly or indirectly. This study aims to isolate and test the rhizosphere and endophytic fungi' ability from Moringa (Moringa oleifera L.) against rice seeds' viability and vigor. Fungus exploration was carried out on soil samples in the rhizosphere and stem and leaf tissue of healthy Moringa plants. Isolation of fungi from the rhizosphere was carried out using 10-2 and 10-3 dilution techniques, while the isolation of endophytic fungi was carried out on the leaf and stem tissue of Moringa, then cultured on potato dextrose agar (PDA) medium. The pathogenicity test of fungi and its effect on in-vitro rice seed germination using the blotter test method, namely growing 25 rice seeds on seven-day old fungal isolates. Nineteen fungal isolates were isolated and collected from the parts of the Moringa plant. Pathogenicity observations showed that there were five fungal isolates as potential pathogens, namely isolates RF2, RF5, RF6, RF8, and EDF6. A total of four fungal isolates tested consistently showed a positive effect on seed viability and vigor with a value of ≥90%, namely isolates RF4, EDF1, EDF2, and EDFbt3.